Demokrasi di Indonesia: Pancasila sebagai Kontekstualisasi Demokrasi - Bolo, Andreas Doweng (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2018)
A critical outlook on democracy in general and Pancasila Democracy in particular is a necessary reflection through the course of times. This paper examines Pancasila democracy in descriptive ways as well as prescriptive way. These approaches are an attempt to explore Pancasila democracy as an open ideology in its essence. In Indonesia’s history, Pancasila democracy was once used as a tool to legitimize power. However, discourses on the subject matter in its nature must be done in the diversity of rational arguments and cannot depend on the interpretations of the ruler alone. When democracy is isolated from rational discourses, it can get caught up in various problems such as “money politics” and “identity politics” which eventually destroy democracy itself. This article portrays the dynamics of democracy in Indonesia, both in its formal settings and as a building that allows humanity reach its dignity. Pancasila Democracy can be a space for a change towards Indonesia that is more animating to the spirit of divinity, humanity, and nationalism and towards a society with solid physical and spiritual well-being.